Synergy between School Principals and Foundation Chairs in Building a Quality Learning Environment - Dwina Putri; Ainur Rofiq (Universitas Muhammadiyah Enrekang, 2023)
This research aims to determine the synergy of top management within the educational foundation in the school's efforts to create a quality educational environment at Albuhari Labuhanbatu Vocational School. The research was conducted using qualitative descriptive methods at Albuhari Labuhanbatu Vocational School 2023. Data collection methods in this research used interview, observation and documentation techniques. Research shows that funds play a role as supervisors, mentors and coaches in implementing the development of a quality learning environment. This is seen in the selective decisions of administrators and the selection of teaching staff. The principal is the engine that drives the process of creating a quality learning environment. Creating a quality learning environment in schools requires three elements: input, process, and results. These three things are interdependent. Without good implementation and learning processes, the results of an educational institution will not be optimal. There are many obstacles in developing a quality learning environment, but with the cooperation and involvement of all parties in the school, such as the foundation and the principal, all of these can be overcome. Foundations, principals, and staff must work together to overcome the challenges that hinder the development of quality learning environments. It can be concluded that the role of the foundation in creating a quality educational environment at Al-Bukhari Labuhan Batu Vocational School has been quite effective. This shows that the Foundation plays an important role and synergizes well with the school principal in developing a quality learning environment at Albuhari Labukhanbatu Vocational School.